2015
DOI: 10.4142/jvs.2015.16.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of bovine viral diarrhea virus strains in Beijing, China and innate immune responses of peripheral blood mononuclear cells in persistently infected dairy cattle

Abstract: To acquire epidemiological data on the bovine viral diarrhea virus (BVDV) and identify cattle persistently infected (PI) with this virus, 4,327 samples from Holstein dairy cows were screened over a four-year period in Beijing, China. Eighteen BVD viruses were isolated, 12 from PI cattle. Based on genetic analysis of their 5'-untranslated region (5'-UTR), the 18 isolates were assigned to subgenotype BVDV-1m, 1a, 1d, 1q, and 1b. To investigate the innate immune responses in the peripheral-blood mononuclear cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Subsequent reports revealed that Pestivirus A−1m is emerging in most of provinces and is considered to be a predominant Pestivirus A genotype in herds (27,30,50,54,57), and also detected in Henan province and neighbor province (29). In addition, sequences of Pestivirus A−1m strains in different regions showed highnucleotide homology, indicating that these strains share the same origin (27,49). Recently, other surveys on goats uncovered that the Pestivirus A−1m could infect goats naturally and cause diarrhea (58).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent reports revealed that Pestivirus A−1m is emerging in most of provinces and is considered to be a predominant Pestivirus A genotype in herds (27,30,50,54,57), and also detected in Henan province and neighbor province (29). In addition, sequences of Pestivirus A−1m strains in different regions showed highnucleotide homology, indicating that these strains share the same origin (27,49). Recently, other surveys on goats uncovered that the Pestivirus A−1m could infect goats naturally and cause diarrhea (58).…”
Section: Discussionmentioning
confidence: 99%
“…Among BVDV-1b genotype, only two BVDV-b1 have been reported in cattle (Zhang et al, unpublished) [2], while the large majority (n = 41) were BVDV-1b2, 13 in cattle, 27 in yaks [2] and one in a Bactrian camel (Camelus bactrianus) [31]. Four bovine strains (Gao et al, unpublished) [6] belonged to genotype BVDV-1.3. Two other bovine strains (S133 and TY05), reported as M [7] [8] resulted BVDV-1.6.…”
Section: Resultsmentioning
confidence: 99%
“…The geographic distribution of genotypes varied considerably, and in certain countries as China, over the half of the 23 genotypes described in the species, 12 could be identified: BVDV-1a, 1b1 and 1b2, 1.3, 1.6, 1.7, 1.8, 1.10, 1.11, 1.15, 1.18, 1.21 and 1.23. BVDV-1a (n = 4) was reported in two bovines [6], two Bactrian camels [31] and one pig [32]. Despite belonging to the same BVDV-1a genotype, strains NH01 (bovine) and SH1060 (pig) were low related, showing 89.2% homology and a divergence of 11 bp in the IRES.…”
Section: Resultsmentioning
confidence: 99%
“…Immune system is the major contributor to host defense against infection and maintaining heath, which consists of immune organs, immunocytes and immune molecules [19,32]. The thymus, one of the most important immune organ, is the location of T-cell development where bone marrow-derived progenitors differentiate to become mature thymocytes before emigration into the periphery as new T cells [14].…”
Section: Discussionmentioning
confidence: 99%